BIOEROSION OF THE PLIO-PLEISTOCENE TRANSGRESSION OF SOUTHERN ITALY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
During the Pliocene and Lower Pleistocene, the structural unit of the Murge was largely submerged by a marine transgression. As the sea advanced, the limestone basement surface was invaded by bioeroding organisms whose borings are well preserved through burial by the calcareous sediments of the Calcarenite di Gravina formation. The tilted—block topography of the submerging Murge unit produced different coastal environments ranging from protected gentle slopes to exposed vertical clifflines. Details of the bioerosion were examined at four localities that cover a range of those environments. The 35 ichnotaxa recognized (excluding microborings) are treated taxonomically where necessary, and their relative distributions and occurrences are studied. Three new ichnospecies are erected: Gastrochaenolites cor, Maeandropolydora barocca and M. crassa. Four recurring assemblages are recognized: Caulostrepsis/ Maeandropolydora assemblage, G. cor assemblage, G. torpedo/ Entobian assemblage and a High Diversity Entobian—Dominated assemblage. All four indicate shallow marine environments, their relative distributions being influenced by environmental factors such as the attitude of the substrate surface and the hydrodynamic energy level.
Keywords: Bioerosion; Trace fossil; Shallow marine; Palaeoenvironmental indicators; Taxonomy.